Material recovery certification for construction workers. Issue 1 (7th September 2020) - Mayer, Matan
Low and zero-carbon building certification programmes typically focus on emissions caused by building operation and/or material extraction and manufacturing activities. However, 'end-of-life' issues involving the reuse, remanufacture or recycling potential of embodied energy-intensive components are often overlooked. As a result, training and certification in this field tends to be diagnostic and observational rather than proactive and anticipatory. To ensure that vocational workers have appropriate capabilities to recycle or reuse building components fully, a training and certification programme is necessary that focuses on end-of-life material recovery potential. A framework is presented for recovery of building products and the certification system for workers. The system rates recovery potential at both the material and assembly levels through a series of evaluation criteria. This assessment is translated into a product labelling scheme as well as a training and certification programme for vocation workers involved in the production, supply and installation chains of recovery-oriented products. Practice relevance: Material recovery training in the built environment is currently limited and lacks a holistic view of the entire recovery chain. A certification system targeting material recovery could help propel a transition to circular consumption models in the built environment. Vocational training based on a full supply chain view of the end-of-life sector would be essential for a transition to a circular economy.